공공보건의료체계 발전 방안에 대한 상대적 중요도 분석 - 김유호; You Ho Kim (보건정보통계학회지, 2018)
Objectives: The purpose of this study is to demonstrate empirically through a specialist AHP analysis what factors should be more important in the development of the public health care system. In addition, we will use Analytic Hierarchy Process (AHP) method for experts to achieve research purpose. Methods: The data analysis method of this study is as follows. First, we set up three metrics in order to measure the relative importance between the factors to be improved for the development of the public health care system and each of the sub-factors. A total of nine measurements (items) were set by combining the three measurement criteria for each measurement index. Second, the relative importance and priority analysis use the AHP analysis. Third, the subjects of this study were 15 experts in the field of public health care. The statistical processing was performed using the Expert Choice 2000 statistical program. Results: In order to development of the public health care system, experts ranked the most important as improvement in the systematic aspect of public health care (56%) as the first priority. Next, the relative importance analysis of the measurement items considering the multiple-weights of the sub-factors is as follows. The strengthen institutional improvement (revitalization of secondary public function hospital) was the number one, strengthen cooperation between agencies was the second, and Re-establishing the role of local public health care system was the third place. Conclusions: Considering the relative importance, factors that are considered to be important in the first place may not be improved as the best policy alternative due to limitations in spatial, temporal, financial, and institutional aspects. In this case, we suggest that we should choose the best policy alternative by using prioritization considering relative weights.